2008
DOI: 10.1002/ctpp.200810079
|View full text |Cite
|
Sign up to set email alerts
|

Emissive Probe Diagnostics in Low Temperature Plasma – Effect of Space Charge and Variations of Electron Saturation Current

Abstract: We report a study of electron saturation current variations at varying probe heating that were found to be closely related to probe wire contamination. The study was performed in three types of low temperature argon plasma -the weakly magnetized plasma of a cylindrical magnetron, the non-magnetized plasma of a double plasma machine and a hollow cathode plasma jet, showing different trends. In the present work the effect of overestimation of the plasma potential by a strongly emitting probe is discussed and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…These discrepancies are still not sufficiently clarified but several thorough investigations were performed recently [9,10,20,21], and future investigations will also include further more realistic computer simulations of emissive electrodes in plasmas of various densities and electron temperatures. See also below.…”
Section: Resultsmentioning
confidence: 94%
“…These discrepancies are still not sufficiently clarified but several thorough investigations were performed recently [9,10,20,21], and future investigations will also include further more realistic computer simulations of emissive electrodes in plasmas of various densities and electron temperatures. See also below.…”
Section: Resultsmentioning
confidence: 94%
“…Also the question is still not satisfactorily answered whether or not the floating potential of even a strongly emissive probe V fl,em will remain below the true value of Φ pl by a value on the order of T e [5,10,11,12,13] if T e is more than one order of magnitude larger than T em , the temperature of the emitted electrons, which in a discharge plasma is usually the case. It was also found that it depends very much on the geometrical form of the probe, especially on how long the wire loop is [14,15]. In particular with a laser-heated probe we found practically no deviation of V fl,em from Φ pl [16] (section 4).…”
Section: Perturbation Of a Magnetized Plasma By An Emissive Probementioning
confidence: 90%
“…In case of space-charge limited regime with emissive probes the emission current is effectively lowered and consequently the measured plasma potential saturates below the actual plasma potential. This has been shown analytically by [16,17] to be of order of kT e and there has been experimental work performed, also in tokamaks, which principally agrees with the proposed theory [12,14], but also work that disagrees [10,18,19]. If we refer to [16] and take their estimation, then a severe mistake of roughly 10-20 V could be made using floating emissive probe method in medium-sized tokamak plasmas.…”
Section: Space-charge Limited Emissionmentioning
confidence: 80%
“…6, where three cases are shown, for a below critical emission, close to critical emission and beyond critical emission. Experimental work has recently been performed on the field of space-charge effects by Marek et al [19] for low-temperature plasma. In our case, however, we do not account for probe surface contamination, neither could we account for variations of electron saturation current, because our case was purely floating.…”
Section: Resultsmentioning
confidence: 99%